2002
DOI: 10.1080/00071660120121436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary oregano essential oil on performance of chickens and on iron-induced lipid oxidation of breast, thigh and abdominal fat tissues

Abstract: 1. We studied the effect of dietary oregano essential oil (50 and 100 mg/kg of feed) on the performance of broilers, and determined the susceptibility of the resulting broiler meat to iron-induced lipid oxidation. 2. Performance of the birds was unaffected by the experimental diets. Therefore, dietary oregano oil exerted no growth-promoting effect on broilers. 3. Iron-induced lipid oxidation showed that as oregano oil increased in the diet, malondialdehyde values decreased in tissue samples, suggesting that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
192
4
30

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(260 citation statements)
references
References 36 publications
11
192
4
30
Order By: Relevance
“…In the present trial, coriander powder supplementation level had no effect (P >0.05) on the carcass traits. This result was in agreement with Case et al (1995), Botsoglou et al (2002), Jang et al (2007) and Amouzmehr et al (2012), who reported that the use of herbal plants had no effect on the dressing percentage of broiler chickens. …”
Section: Resultssupporting
confidence: 91%
“…In the present trial, coriander powder supplementation level had no effect (P >0.05) on the carcass traits. This result was in agreement with Case et al (1995), Botsoglou et al (2002), Jang et al (2007) and Amouzmehr et al (2012), who reported that the use of herbal plants had no effect on the dressing percentage of broiler chickens. …”
Section: Resultssupporting
confidence: 91%
“…Concerned about the possible negative effect of garlic processing on its active substances, FREITAS et al (2001) worked with fresh garlic, using it at 0.6% in broiler diets, but also no performance benefits were observed. BOTSOGLOU et al (2002) indicated that dietary oregano oil exerted no growth promotion on broilers when supplemented the feed at 50 or 100mg.kg -1 . On the other hand, JAMROZ & KAMEL (2002) observed improvements in daily gain (8.1%) and in feed conversion ratio (7.7%) of chickens when fed with diets supplemented (300mg.kg -1 ) with a plant extract containing capsaicin, cinnamaldehyde, and carvacrol.…”
Section: Phytogenic Additive As An Alternative To Growth Promoters Inmentioning
confidence: 99%
“…Assim como no animal vivo, a oxidação representa uma das principais causas de deterioração de alimentos para consumo humano (FELLENBERG & SPEISKY, 2006). Ainda que o efeito de antioxidantes naturais e o dano oxidativo em alimentos tenham sido amplamente pesquisados (LOPEZ-BOTE et al, 1998;BOTSOGLOU et al, 2002), estudos avaliando a peroxidação lipídica plasmática in vivo são escassos, ratificando a importância da realização deste trabalho e, além disso, evidenciando a necessidade de estudos futuros nesse contexto.…”
Section: Resultsunclassified
“…No entanto, o uso desses antibióticos vem sofrendo restrições nos últimos anos, devido à possibilidade de seleção de microorganismos resistentes, desenvolvimento de resistência bacteriana cruzada em humanos e devido à exigência de produtos livres de resíduos de antibióticos pelo mercado consumidor (BUTAYE et al, 2003;SALEHA e al., 2009). Como alternativa, tem-se a substituição por metabólitos secundários de plantas como os óleos essenciais, já que eles possuem potencial antimicrobiano (FARAG et al, 1989;KAMEL, 2000;TZAKOU et al, 2001), além de possuírem função imunomoduladora (MELLOR, 2000), propriedades antioxidantes e de conservação dos alimentos (FARAG et al, 1989;BOTSOGLOU et al, 2002). Recentemente, foi demonstrado que frangos de corte alimentados com óleos essenciais de orégano, sálvia, alecrim e extrato de pimenta (OLES) obtiveram peso final e ganho de peso similares àqueles observados em animais suplementados com antibióticos promotores de crescimento.…”
Section: Introductionunclassified
See 1 more Smart Citation